Energy Cultures in the European Union - Rosicki, Remigiusz (WNPiDz UAM, 2016)
The main objective of the text is to present an analysis that points to the existence of special “energy cultures” in the European Union. The comparative analysis encompassing the results of previous research into “energy cultures” employs statistical methods, i.e. a cluster analysis (Ward’s clustering method and k-means clustering method). The main sections of the text address: (1) the concept and examples of “energy cultures,” (2) a methodology of analysis, (3) a selection of indexes characterising “energy cultures,” (4) an attempt at grouping the European Union member states with the aid of clustering, (5) conclusions. With a view to making the research problem more specific, the present text features the following questions: (1) Is the claim that the European Union manifests special “energy cultures” legitimate?, (2) Did the decade of 2001-2011 witness changes in the field of the European Union “energy cultures,” as earlier recognised by the literature?
The main object of the analysis presented in the text was to point to and confirm the existence of special “energy cultures” in the European Union. In order to achieve this aim the use was made of research present in the literature, inter alia, in the publications containing statistical analyses by: (1) A. Pach-Gurgul, (2) P. Tapio and his research team – Banister, J. Luukkanen, J. Vehma i R. Willamo, also in a review, (3) Z. Łucki and W. Misiak. Compared with the invoked research, the timeframe of the analysis in the text covered 2011, and the subjective scope embraced 28 countries (EU-28). As part of the research process the following research hypotheses were subjected to verification: (1) It must be assumed that the dissimilarities in energy structures of particular EU member states are an outstanding premise on which to base a recognition of the existence of specific “energy cultures” in the European Union, (2) It must be assumed that in the period of 2001-2011 there occurred changes in the area of “energy cultures” of the European Union, which had earlier been recognised in the literature. In this scope the following conclusions ought to be presented: I. CONCLUSIONS: The differences in energy structures result in the possibility of pointing to particular features characterising member states and clusters of countries, partially because of the predominance of specific energy carriers and/or a way of their conversion. On account of the use of selected indexes for the purpose of characterising the specificity of the European Union member states, six clusters have been distinguished, and they include the following countries: (1) Spain, France, Italy and Great Britain; (2) Bulgaria, the Czech Republic, Estonia and Poland; (3) Denmark, Ireland, Greece, Cyprus, Malta, Austria, Slovenia, Finland and Sweden; (4) Croatia, Latvia, Lithuania, Hungary, Portugal, Romania and Slovakia; (5) Germany; (6) Belgium, Luxembourg and the Netherlands. An observable cluster that recurs in the research by A. Pach-Gurgul as well as in the analysis presented in the text covering 2011, embraces Bulgaria, the Czech Republic, Estonia and Poland (Cluster II). As for Ward’s method the cluster is broader, but features an outstanding group of the above-mentioned countries (also including: Croatia, Latvia, Lithuania, Hungary, Slovakia and Romania). Besides, in this model, in comparison with A. Pach-Gurgul’s research, another cluster is by and large repeated, including Croatia, Latvia, Lithuania, Hungary, Portugal, Romania and Slovakia – Cluster IV (for a variety of reasons Croatia and Portugal are not repeated). The characteristic feature of both clusters is a higher scale of the index of energy intensity (kgoe/€1000). This shows that it is legitimate to recognise the existence of the division of the European Union into the two “energy cultures”: the Western European one and Eastern European one. The main factor behind this division is the energy intensity of the economies of individual member states. Unlike the analysis by P. Tapio and his research team, the axis of division has changed considerably, for within the so-called “old” European Union (EU-15) there was an observable general division into the Northern European and Southern European “energy cultures.” Both the above-mentioned clusters (II and IV) can be associated with the “Eastern European culture” as part of the division presented by Z. Łucki and W. Misiak. The energy culture distinguished by the two researchers is to be characterised by: (1) a variety of energy policies, (2) a high energy intensity of the economy, (3) a low electric energy consumption, (4) limited awareness, (5) a negative attitude towards energy market liberalisation. In the case of Bulgaria, the Czech Republic and Poland (Cluster II), the characteristic feature is a considerable share of solid fuels in the energy mix of the gross inland energy consumption. The countries included in Cluster IV are characterised by a smaller share of solid fuels and a higher diversity of energy structure. As part of the k-means clustering method, it is worth pointing out two clusters of countries: Cluster I (Spain, France, Italy, Great Britain) and Cluster V (Germany). The countries in both clusters belong to the so-called “old” European Union, and their main feature is a substantial level of energy production, Germany being the largest producer. In both cases, the characteristic features are a marked share of renewable energy sources, gas as well as petroleum and petroleum products in the gross inland energy consumption. Furthermore, both clusters are characterised by a low or relatively low index of energy intensity (kgoe/€1000). As part of the clustering based on the k-means method, in both periods, that is in 2001 and 2011 the cluster comprising Belgium, Luxembourg and the Netherlands was repeated. This cluster is characterised by a high index of energy consumption per capita and a high index of GHG emission per capita. II. CONCLUSIONS: It must be emphasised that the period 2001-2010 is connected with the transition process of the electric energy and gas sectors in the European Union. The process is also associated with the introduction of the 1st Climate-Energy Package in the European Union. What is more, the changes will be continued on account of the efforts at building an Energy Union as well as the implementation of the so-called 2nd Climate-Energy Package. Of particular significance is also the increase in the import dependence of the European Union, given the declining reserves of energy resources. Moreover, the objectives of the “green energy policy” will be giving rise to the increasing energy efficiency and the growing share of renewable energy sources in energy production, which may constitute a factor limiting the import dependence. Thus, it should be posited that in the long term we will be witnessing a homogenisation of indexes, e.g. the index of energy intensity. These processes may result in the tendency for changes towards the model of the “energy culture,” which Z. Łucki and W. Misiak have termed a “Scandinavian culture,” that is one characterised by the following features: (1) a development of RES, (2) a low consumption of coal, (3) a low index of GHG emission, (4) a considerable energy consumption, (5) a low energy intensity, (6) a heightened environment- and energy-consciousness. By way of comparing the analyses for 2011 and for 2001, based on the k-means clustering method, it must be stressed that Belgium, Luxembourg and the Netherlands hold steady in the cluster (Cluster VI), whereby they abide by the roles played by the features earlier ascribed to them. A measure of stability can also be observed in the case of Spain, France, Italy, Great Britain and Germany (Clusters I and V). Noteworthily, Sweden has been eliminated from the group (despite lowering the scale of the first three indexes). The distinctive feature of Eastern European countries is the high scale of the energy intensity index, as viewed against the backdrop of Clusters I and IV. Yet, some tendency towards stirring of the scale of energy intensity index is to be observed in this scope. A transformation of the energy structure will also prove quite a challenge here. Poland can serve as an example, whereby coal will continue to be the country’s main electric energy carrier for the next 30 years. The comparative analysis featuring in the text is limited, and so it does not address all the issues concerned with the correlations between the presented “energy cultures.” The work sets out to verify the results of the research into the existence of “energy cultures” in the European Union, as presented by A. Pach-Gurgul, Z. Łucki and W. Misiak as well as P. Tapio and his research team. Still, the greatest emphasis has been laid on the proposals made by A. Pach-Gurgul, for it was her publication as well as the selection of indexes and research tools included therein that proved to be an inspiration for the present text. It should also be noted that the object of analysis in the text does not embrace a discussion of the legitimacy of employing specific methods for clustering.
Keywords: Energy cultures; kultury energetyczne; Indexes of energy cultures; wskaźniki kultur energetycznych; Energy policy; polityka energetyczna; Energy security; bezpieczeństwo energetyczne; European Union; Unia Europejska